Analysis of Waikelo Port Breakwater Failure through 2D Wave Model - Winarta, Bambang; Damarnegara, A. A. N Satria; Anwar, Nadjadji; Juwono, Pitojo Tri (Civil and Environmental Science Journal (CIVENSE), 2018)
Waikelo Port is located in South West Sumba of East Nusa Tenggara. The port facilities are protected by breakwater with a vertical wall construction and it was built in a relatively deep ocean at -15m of Low Water Sea Level (LWS). On 21 of January 2012, an earthquake with magnitude of 6.3 Richter scale occurred around Sumba Island and it caused cracking in the concrete wall of breakwater. Then, 4 days after on 25 st January 2012, a heavy wind of 20–23 knots generated a high wave around 4.0–5.0m in Sumba strait. These high waves caused a critical damage on the west part of the breakwater. The damage of port facilities were getting worse when a storm called Lua hit on March 2012. This study was conducted to observe the effect of the extreme event in the failure of breakwater. The result of two-dimensional (2D) wave model shows that the wave heights in the area of breakwater are varied 3.80 to 4.0m. It is quite greater than the wave design of 50 years return period (= 2.00m) which was used in breakwater design and calculation. This observable fact confirms that the failure of breakwater was caused by the continuous extreme events that exceed the design criteria